Educational strategy to favor attitudes towards statistics in engineering students - Olazábal, Raul León Báez; Valdés, Doris Vivian Prieto; Anarela, Alexia Esther Nardin; Prieto, Raidel Báez (Ciência e Natura, 2022)
The increase in the need of teaching and learning of statistics leads to new research in this area. An exploratory study is presented, during the 2018-2019 school year, to analyze the attitudes towards the statistics, that students of the civil engineering career have at the University of Camagüey, Cuba. Based on experiences validated by the experts Estrada (2002, 2007) and Auzmendi (1992), the application of an educational strategy with three stages is proposed. It is based, applied and evaluated in the characterization of the second-year students of Civil Engineering and the diagnosis of their attitudes towards Statistics. The results show, that the implementation of this methodology, allowed to increase the positive attitude towards statistics and encourage better learning of the teaching process.